The Role of Diatomite Particles in the Activated Sludge System for Treating Coal Gasification Wastewater - 张文启 饶品华 张辉 徐菁利 (Chinese journal of chemical engineering, 2009)
Diatomite is a kind of natural low-cost mineral material. It has a number of unique physical properties and has been widely used as an adsorbent in wastewater treatment. This study was conducted to investigate the aerobic biodegradation of coal gasification wastewater with and without diatomite addition. Experimental results indicated that diatomite added in the activated sludge system could promote the biomass and also enhance the performance of the sludge settling. The average mixed-liquor volatile suspended solids （MLVSS） is increased from 4055 mg.L^-1 to 4518 mg.L^-1 and the average settling volume （SV） are changed only from 45.9% to 47.1%. Diatomite additive could enhance the efficiency of chemical oxygen demand （COD） and total phenols removal from the wastewater. The COD removal increased from 73.3% to near 80% and the total phenols removal increased from 81.4% to 85.8%. The mechanisms of the increase of biomass and pollutants removal may correlates to the improvement of bioavailability and sludge settlement characteristics by diatomite added. Micrograph of the sludge in the diatomite-activated sludge system indicated that the diatomite added could be the carrier of the microbe and also affect the biomass and pollutant removal.